Keeping girls in sport: a two-part evaluation of an e-learning program for coaches and activity leaders - Szabo, S. W.; Owen, E. C.; Kennedy, M. D.; Knight, C. J. (International Sport Coaching Journal, 2024)
The purpose of this study was twofold: first, to identify who engaged with the Keeping Girls in Sport e-learning program and, second, to evaluate coach and activity leaders` perceptions of the program and their perceived learnings gained from completing the program. An explanatory sequential mixed-method design was adopted. First, an online survey was distributed to all individuals who had participated in the program. In total, 511 (33% response rate) completed the survey. Quantitative survey data were analysed using descriptive statistics. Subsequently, interviews were conducted with 20 survey respondents. A realist logic of analysis was applied to the qualitative data, and context-mechanism-outcome configurations were formed. Overall, survey findings indicated that most participants identified as women (56%), coaches (69%), and were between 40 and 49 years of age (37%). In general, participants had positive perceptions of the program. Participants perceived that the accessibility and flexibility of the program increased opportunities to engage with content and, thus, their learning. They described improvements in knowledge and perspective regarding working with female athletes. This increase in knowledge provided participants with confidence to establish trusting and positive relationships with others, specifically parents. Nevertheless, participants highlighted a need for more tailored but also more expansive programs.